Causes and effects of wine tourism development in wineries: The perspective of institutional theory. Issue 3 (15th August 2016) - Lavandoski, Joice; Pinto, Patrícia; Silva, João Albino; Vargas-Sánchez, Alfonso
Abstract : Purpose: This study aims to propose that the institutional environment exerts pressure on the behavior of wineries toward wine tourism development (WTD) and the effect of this influence confers legitimacy to the business of wine tourism. Design/methodology/approach: Structural equation modeling through partial least squares was applied to estimate and validate a model using data from a quantitative survey in the universe of 62 wineries with a wine tourism component along the Alentejo Wine Route in Portugal. The proposed model is based on institutional theory through an inter-organizational perspective of wineries. Findings: The results show that WTD coexists with a highly institutionalized environment, exerting distinctive mechanisms of external pressure together with the search for social legitimacy through actions and practices on the part of the involved wineries. However, the relationship between legitimacy and organizational performance in wineries with wine tourism is not validated. Research limitations/implications: The specific sample of the Alentejo wine companies does not allow the results to be generalized. Future studies should replicate the proposed research model using other geographic areas. Practical implications: The results are particularly interesting for managers of wineries and should be considered in the decision-making and strategic processes regarding wine tourism. Originality/value: The use of institutional theory in the wine tourism context is novel and original. This study fills a research gap by conducting an empirical investigation of wine tourism based on institutional theory, which allows the identification of exogenous factors that can influence and impose restrictions on the organizational behavior of winery companies toward wine tourism.